Respuesta :

d) You have a difference of squares:

49y² - 9 = (7y)² - 3²

Recall the identity,

a² - b² = (a - b) (a + b)

So,

49y² - 9 = (7y - 3) (7y + 3)

e) Pull out the common factor 3 from each term:

3x² - 3x - 90 = 3 (x² - x - 30)

Now use the sum-product method. Notice that we can write 30 = 5 • 6, and 5 - 6 = 1, so

3x² - 3x - 90 = 3 (x + 5) (x - 6)

f) Same as in (e), use the sum-product method. Notice that 42 = 7 • 6, and -7 - 6 = -13, so

x² - 13x + 42 = (x - 7) (x - 6)

#1

  • 49y²-9
  • (7y)²-3²
  • (7y-3)(7y+3)

#2

  • 3x²-3x-90
  • 3(x²-x-30)
  • 3(x-6)(x+5)

#3

  • x²-13x+42
  • x²-7x-6x+42
  • (x-7)(x-6)